Detection and Accurate Localization of Circular Fiducials under Highly Challenging Conditions - Calvet, Lilian; Gurdjos, Pierre; Griwodz, Carsten; Gasparini, Simone (2016 IEEE Conference on Computer Vision and Pattern Recognition (CVPR), 2016)
Using fiducial markers ensures reliable detection and identification of planar features in images. Fiducials are used in a wide range of applications, especially when a reliable visual reference is needed, e.g., to track the camera in cluttered or textureless environments. A marker designed for such applications must be robust to partial occlusions, varying distances and angles of view, and fast camera motions. In this paper, we present a robust, highly accurate fiducial system, whose markers consist of concentric rings, along with its theoretical foundations. Relying on projective properties, it allows to robustly localize the imaged marker and to accurately detect the position of the image of the (common) circle center. We demonstrate that our system can detect and accurately localize these circular fiducials under very challenging conditions and the experimental results reveal that it outperforms other recent fiducial systems.